TWO GENIUSES. DIFFERENT ERAS AND DIFFERENT CULTURES - Мехрибон Аминджановна Юсупы; Артыкова Одила Мансурбековна (Journals Park Publishing, 2023)
Alisher Navoi and Alexander Sergeevich Pushkin. What does Alisher Navoi and A.S. Pushkin have in common, two geniuses of world culture, despite the centuries separating their lives, and what do we, contemporaries, have in common with them, what thoughts of poets are close to us, how their work helps us live in new historical conditions, it echoes the thoughts of what identical topics these great people raise in their work.